2022
DOI: 10.3389/fmed.2022.968081
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of synaptotagmin family members in cancers: Recent advances and prospects

Abstract: With the continuous development of bioinformatics and public database, more and more genes that play a role in cancers have been discovered. Synaptotagmins (SYTs) are abundant, evolutionarily conserved integral membrane proteins composed of a short N-terminus, a variable linker domain, a single transmembrane domain, and two C2 domains, and they constitute a family of 17 isoforms. The synaptotagmin family members are known to regulate calcium-dependent membrane fusion events. Some SYTs play roles in hormone sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…There is not much evidence of SYT10 taking any major part in cancer proliferation and cellular pathway regulation leading to tumorigenesis, but as previous studies suggest (Tsutsui et al, 2015;Zhu et al, 2021;He et al, 2022), SYT10, as a syanptotagmin family member, may play a role in drug resistance in ESCA and thus contribute to poor survival and prognosis. A detailed recent review study on potential roles of SYT family members in cancers has been properly described elsewhere (Suo, Xiao and Wang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There is not much evidence of SYT10 taking any major part in cancer proliferation and cellular pathway regulation leading to tumorigenesis, but as previous studies suggest (Tsutsui et al, 2015;Zhu et al, 2021;He et al, 2022), SYT10, as a syanptotagmin family member, may play a role in drug resistance in ESCA and thus contribute to poor survival and prognosis. A detailed recent review study on potential roles of SYT family members in cancers has been properly described elsewhere (Suo, Xiao and Wang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…SYT1 protein is a member of the synaptotagmin family and is a membrane transport protein consisting of an N terminus, a variable link domain, a single transmembrane domain, and two C2 domains (C2A, C2B), with C2 domains serving as Ca 2+ -binding sites. 34 Overexpression of SYT1 was found to promote the invasion and metastasis ability of colon cancer cell lines in vitro . We found that L1PA2-SYT1 was the most frequent event in bladder cancer cell lines and was associated with poor prognosis in patients, and in vitro overexpression of L1PA2-SYT1 enhances the invasion capability of bladder cancer cell line, suggesting the potential tumor-driving role and clinical application potential of L1PA2-SYT1.…”
Section: Discussionmentioning
confidence: 99%
“…Three of them in particular, isoforms VII, VIII, and XIII, have been found to play an important role in the onset and progression of gastric, colon, and other cancers. 128 This makes them a promising therapeutic target for treating PM. Studies showed that synaptotagmin XIII ( SYT13 ) plays a role in the spread of gastric cancer and among patients with recurrent or PM expressing significantly higher levels of SYT13 than those in stage I.…”
Section: Introductionmentioning
confidence: 99%